First, note that radical 4 is 2. So 3xradical 4 is just 6, Now we have 6+2 radical 3. You can't do much with this except factor out a 2 if you want 2(3+Radical 3)
3 sqrt(6) x sqrt(6) = 18
D.2√3
10.3923, approx.
(6√5)/√3 since the index is the same and both numbers are positive, we can write = 6(√5/3) multiply inside the radical by 3/3 to make the denominator a perfect square number = 6(√15/9) = (6/3)√15 = 2√15
radical 3 or 6
Radical(27) can be simplified to 3*radical(3), so the correct answer is 6*radical(3).
√18
6 radical 6
3^3*radical(128) = 3^3*radical(2^7) = 3^3*radical(2^6*2) =3^3*2^3*radical(2) = 216*radical(2).
First, note that radical 4 is 2. So 3xradical 4 is just 6, Now we have 6+2 radical 3. You can't do much with this except factor out a 2 if you want 2(3+Radical 3)
3 sqrt(6) x sqrt(6) = 18
If we read this carefully, what you're asking for is (4 of something) minus (1 of the same thing). The result is 3 of them . . . 3 radical 6.
D.2√3
12 radical 6 x 6 radical 6 = 72 x 6 = 432
radical 30
4 radical 6